INTEGRASI KURIKULUM 2013 DAN PONDOK PESANTREN DI SEKOLAH MENENGAH PERTAMA SWASTA ISLAM TERPADU AL-FURQON TEBAS - Iswadi; Aslan; Sri Sunantri (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2022)
The educational process cannot be separated from changes that occur both in the cognitive, effective and psychomotor domains. However, from these changes there are permanent changes and some are independent of the education provided to students, either through education in the family, school or community. Currently, the implementation of the 2013 Curriculum is being practiced by combining existing learning in schools and Islamic boarding schools, and seeing how the integration model has been developed and the collaboration of Curriculum 2013 subjects in Islamic religious education subjects in particular and Islamic boarding schools in the Al-Islamic Integrated Junior High School. Furqon Tebas. Given the learning of Islamic subjects is a core learning because it is related and has implications for everyday life, so it is necessary to establish the values of spiritual attitudes that can be integrated in the subjects and the teaching and learning process. In relation to this, it is necessary to have an educational institution that collaborates between religious education and general education based on pesantren.